PEMBANGUNAN UNDERPASS KM 319 + 370 ANTARA BUMIAYU – KRETEK LINTAS CIREBON – KROYA DENGAN METODE PENYANGGA - Dwi Sri Wiyanti (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2011)
AbstractA railroad crossing that intersects with a road is called a plot railway or also known as railway cross level. The railway cross level is a railroad that crosses in the same level (at the junction area) with roads, paths, or other railways without using a bridge/link. With a plot railway, the risk of traffic accidents between vehicles and train will be even greater. This is because on the railway cross level there is an intersection between road transport modes and that of train (that have different movement characteristics) on the same field so that it has a high-risk traffic accident.The risk of accidents like that on the railway cross level could be solved with a railroad crossing that is not at the same plot like the underpass. On the underpass, because the track used by the vehicles and trains are different, they do not affect each other. By making observations on the underpass construction project across Cirebon KM 319 +389 – Kroya, it can be concluded that with a good construction method the project will run smoothly according to the planned target without disrupting the schedules of trains that pass above.  Key word : underpass, railway cross level, lintas Cirebon – Kroya, construction method